Rancang Bangun Monitoring Level Muka Air Tanah Di Perkebunan Lahan Gambut Menggunakan SMS Sebagai Pengirim Informasi Data Berbasis Mikrokontroler - Eka Prastia, I Wayan; Arta Wijaya, I Wayan; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 6 No 1 (2019): Jurnal SPEKTRUM, 2019)
The fires of peatlands on oil palm plantations are very vulnerable to occur in the dry season. Fires will arise due to a decrease in the surface of the water resulting in the top layer of peatland becoming dry. Manually monitoring ground level is very difficult. The solution is to make a remote water level monitoring prototype in order to be able to regulate irrigation on peat land and make the system open and close the irrigation door during the dry season and when the rainy season arrives. The design of groundwater level monitoring uses a program installed on the Arduino Uno microcontroller.Water level data is sent by prototype via GSM SIM 800L network, 8 level conditions that have been determined from a depth of 15 cm multiples of five so on to 55 cm. HC-SR04 Ultrasonic Sensor is a detector for water level. Data can be accessed at any time via SMS by sending "Check" to the prototype. The results of the tests performed indicated that the tool can function in accordance with the design and send information as well as receive monitoring orders.